Analysis of Patients Complaints Reviewed from Human Resources Factors, Health and Private Facilities Services - Danang Sasongko; Sentot Imam Suprapto; Indasah Indasah (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2019)
Services provided by hospitals sometimes cause dissatisfaction, dissatisfaction can be conveyed through patient complaints, patient complaints can be caused by factors of human resources, health services or available facilities. The purpose of this study was to determine the factors that influence patient complaints in the Inpatient Room of the Caruban Hospital Pavilion in Madiun Regency. In this study, researchers used an observational research design with a Cross Sectional approach. The sample in this study amounted to 80 respondents. Purposive sampling technique. The research instrument uses a questionnaire with ordinal regression statistical test with α = 0.05. Most respondents 57.9% (113 people) stated that Human Resources in the Inpatient Room were good. Most respondents 53.8% (105 people) stated that health services in the Inpatient Room were good. Almost half of the respondents 46.2% (90 people) stated that the factors of facilities and infrastructure in the Inpatient Room were good. The majority of respondents 53.8% (103 people) showed patient complaints in the low inpatient room. There was an influence of Human Resources with complaints from patients in the Inpatient Hospital of Caruban Hospital in Madiun Regency, p = 0040. there was no influence of health services with complaints of patients in the Inpatient Room of the Caruban Hospital of Madiun District, p = 0.193. There is an influence of facilities and infrastructure with patient complaints in the Inpatient Care Unit of Caruban Hospital in Madiun Regency, p = 0.048. The most influential factor on patient complaints in the Inpatient Pavilion is a factor of human resources and facilities and infrastructure factors because with good resources the service will be excellent supported by the existing facilities and infrastructure.